Marketing polityczny na przykładzie witryn internetowych kół poselskich i klubów parlamentarnych w Sejmie RP VI kadencji - Schroeder-Polak, Marta (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Contemporary political marketing is increasingly using the Internet for its actions. The subject of this article is to analyze this phenomenon in the context of Polish Parliamentary Clubs’ websites. Elements such as page layout, subpages, available information or references to social networking sites were considered. The fundamental question in this article was whether and how Parliamentary Clubs exploit new opportunities?